Synthesis of Functionalized Azet-2(1H)-imines through [2+2] Cycloaddition of Imines and Ketenimines - Yavari, Issa; Nematpour, Manijeh (Synlett, 2013)
The reaction between ketenimine intermediates, generated from terminal alkynes and sulfonyl azides, trichloroacetonitrile, and sodium arylsulfinates in N,N-dimethylformamide at room temperature affords N-[3-aryl(alkyl)-4-arylazet-2(1H)-ylidene]-arene(alkane)sulfonamides in moderate to good yields.
Keywords: 2-azetines; copper iodide; trichloroacetonitrile; sodium arylsulfinates; ketenimines; sulfonyl azides; terminal alkynes